Prioritisation of barriers for supply chain management implementation in the Malaysian automotive industry - Anis,Azilah (2022)
Abstract Paper aims Several Barriers impede the robust effectiveness of the supply-chain management implementation for the Malaysian automotive industry. The purpose of the present work is to identify these Barriers and prioritize them. Originality Originality of the present work lies in identifying the Barriers, putting them into categories and subsequently prioritize them by applying a scientific method such as Analytic Hierarchy Process (AHP).Research Research method This study has identified five main categories of Barriers through literature reviews. Fourteen practitioners who are involved with the automotive industry helped prioritise those Barriers by applying the AHP.Main Main findings Five main categories of Barriers are found to be technological, organisational, individual, strategic, and cultural barriers. Organisational barrier is the most critical barrier followed by technological and strategic barriers. Implications for theory and practice This research provides important feedback to the automotive company managers to take appropriate measures to minimise negative impacts of the barriers identified.